KABUT ASAP DI KOTA JAMBI: RESPONS KAUM PEREMPUAN TERHADAP DEGRADASI LINGKUNGAN - Rizki Takriyanti; Welyne Jeffrey Jehom; Arfan Aziz (Universitas Andalas, 2015)
The air condition in the city of Jambi getting hot. Smog haze occurs almost every year since 1997. On the other hand, attempts to perform the actions that are environmentally friendly as well have been started. Economic and educational level of the woman citizens influence the sensitivity and attitudes towards environmental issues such as air emissions, flooding and waste management. The research underlying this article -about women's attitudes towards the Jambi city’s environment- through qualitative method, find that almost all the informants agree to protect the environment and air, but also almost all of the informants did not agree to pay the levy for air quality improvement. Awareness to protect the environment and the air has started and implanted since kindergarten. Awareness to maintain air quality continues to be done, both by the government, and social units who want a better Jambi city environments.